UiT University Library Private Archive No. 20 : UIT EISCAT ARCHIVES, 1969–2014 - Aspaas, Per Pippin; Magnaudeix, Léa (DataverseNO, 2019)
EISCAT (European Incoherent SCATter Scientific Association) was founded in 1975. It is a collaborative effort in the study of the upper atmosphere, in which major research institutes and funders in France, Britain, Germany, Norway, Sweden, and Finland have joined forces (Japan, China, and Ukraine have since joined, whereas France, Britain, and Germany have either scaled down or closed their participation completely). Sumptuous research facilities in the form of radar transmitters and receivers have been established at Ramfjordmoen, Kiruna, Sodankylä, Kilpisjärvi, and Longyearbyen. The main centre of coordination is located in Kiruna, and has been so since the outset. The UiT EISCAT Archive is thus not an official archive mirroring that of the EISCAT headquarters. Rather, it consists of materials assembled by scientists from UiT that have been involved with EISCAT over the years (predominantly prof. Asgeir Brekke, but also, from the earliest period, Olav Holt and Egil Leer). Apart from official annual reports, the UiT EISCAT Archive contains a variety of supplementary documents (speeches, letters, drafts, notes, photographs, etc.) related to EISCAT. Contents are predominantly in English, with some presence of documents in Norwegian, French, German, Chinese, and Japanese. In the summer of 2014, the archive was transferred from the Auroral Observatory to the University Library. It was systematised and catalogued by MA student Léa Magnaudeix from the Université de Toulouse as part of her internship at the UiT Library in the spring semester 2019. The original system was largely retained, although some duplicates were discarded and plastic and metal gadgets removed from the papers. The dataset contains a comprehensive catalogue of all documents in the archive.